Annotated Corpus for Sentiment Analysis in the Uzbek Language - Babadjanov E.S.; Saidrasulov Sh.N. (Uzbekistan Open Conference, 2025)
This study examines the methodology for creating an annotated corpus for sentiment analysis in the Uzbek language. Unlike high-resource languages with large annotated corpora, resources for the Uzbek language remain limited. The study analyzes international experience and proposes a methodology for developing a corpus adapted to the linguistic characteristics of the Uzbek language. The proposed approach contributes to the development of more accurate and reliable sentiment analysis models for Uzbek.
Keywords: Sentiment analysis; annotated corpus; Uzbek language; text classification; NLP